Understanding the squamous cell carcinoma immune microenvironment - Saeidi, Vahide; Doudican, Nicole; Carucci, John A. (Frontiers in Immunology, 2023)
Primary cutaneous squamous cell carcinoma (cSCC) is the second most common human cancer with a rising incidence of about 1.8 million in the United States annually. Primary cSCC is usually curable by surgery; however, in some cases, cSCC eventuates in nodal metastasis and death from disease specific death. cSCC results in up to 15,000 deaths each year in the United States. Until recently, non-surgical options for treatment of locally advanced or metastatic cSCC were largely ineffective. With the advent of checkpoint inhibitor immunotherapy, including cemiplimab and pembrolizumab, response rates climbed to 50%, representing a vast improvement over chemotherapeutic agents used previously. Herein, we discuss the phenotype and function of SCC associated Langerhans cells, dendritic cells, macrophages, myeloid derived suppressor cells and T cells as well as SCC-associated lymphatics and blood vessels. Possible role(s) of SCC-associated cytokines in progression and invasion are reviewed. We also discuss the SCC immune microenvironment in the context of currently available and pipeline therapeutics.